THE BATCH CARBONISATION OF COCONUT SHELL WITH WASTE HEAT RECOVERY - G R Breag; H C Coote; A C Hollingdale (International Coconut Community Journal, 1989)
Technology developed by ODNRI for waste heat recovery during carbonisation of coconut shell has been succesfully adopted by the desiccated coconut industry in Sri Lanka. The initial development and design of the unit has been described elsewhere (Breag et al, 1984) and also the broader issues of the technology in relation to the Sri Lankan coconut industry have been examined (Breag et al. 1985). In the five year period since the first prototype trial was carried out, the Coconut Development Authority, Sri Lanka assisted by ODNRI, has disserninated knowledge of the technology and promoted manufacture of the equipment. At this time there are 15 units installed of the basic 8M3 capacity system and a prototype 16m3 capacity unit has been commissioned recently. The units are manufactured by a number of local companies and are now being supplied to mill owners on a purely commercial basis. This paper provides a cost benefit financial analysis for the standard 8m3 capacity unit using the data acquired from accumulated,operating experience.